Beyond Misinformation: Understanding and Coping with the "Post-Truth" Era - Lewandowsky, Stephan; Ecker, Ullrich K. H.; Cook, John (Journal of applied research in memory and cognition, 2017)
The terms "post-truth" and "fake news" have become increasingly prevalent in public discourse over the last year. This article explores the growing abundance of misinformation, how it influences people, and how to counter it. We examine the ways in which misinformation can have an adverse impact on society. We summarize how people respond to corrections of misinformation, and what kinds of corrections are most effective. We argue that to be effective, scientific research into misinformation must be considered within a larger political, technological, and societal context. The post-truth world emerged as a result of societal mega-trends such as a decline in social capital, growing economic inequality, increased polarization, declining trust in science, and an increasingly fractionated media landscape. We suggest that responses to this malaise must involve technological solutions incorporating psychological principles, an interdisciplinary approach that we describe as "technocognition." We outline a number of recommendations to counter misinformation in a post-truth world. General Audience Summary Imagine a world that considers knowledge to be "elitist." Imagine a world in which it is not medical knowledge but a free-for-all opinion market on Twitter that determines whether a newly emergent strain of avian flu is really contagious to humans. This dystopian future is still just that-a possible future. However, there are signs that public discourse is evolving in this direction: terms such as "post-truth" and "fake news," largely unknown until 2016, have exploded into media and public discourse. This article explores the growing abundance of misinformation in the public sphere, how it influences people, and how to counter it. We show how misinformation can have an adverse impact on society, for example by predisposing parents to make disadvantageous medical decisions for their children. We argue that for countermeasures to be effective, they must be informed by the larger political, technological, and societal context. The post-truth world arguably emerged as a result of societal mega-trends, such as a decline in social capital, growing economic inequality, increased polarization, declining trust in science, and an increasingly fractionated media landscape. Considered against the background of those overarching trends, misinformation in the post-truth era can no longer be considered solely an isolated failure of individual cognition that can be corrected with appropriate communication tools. Rather, it should also consider the influence of alternative epistemologies that defy conventional standards of evidence. Responses to the post-truth era must therefore include technological solutions that incorporate psychological principles, an interdisciplinary approach that we describe as "technocognition." Technocognition uses findings from cognitive science to inform the design of information architectures that encourage the dissemination of high-quality information and that discourage the spread of misinformation.